Migração e cultura(s) : acessos, desafios e vivências de haitianas(os) em Cuiabá-MT - Magalhães, Acimar da Costa (2023)
The research aimed at understanding the overall process of igration/settlement of some Haitian individuals in Cuiabá-MT, in the year 2014. The specific objectives were as follows: a) to determine if, in any way, state public policies promote inclusion for immigrants; b) to identify, on-site, the difficulties faced by Haitian individuals, highlighting them within the following parameters: language, integration into the job market, education, and reception; c) to recognize the percentage of unemployed individuals in this population and those who are in the informal sector; d) to ascertain the variables causing unemployment, as well as how this surplus workforce could be better utilized, based on skills and professional qualifications; e) to uncover whether cultural, linguistic, and professional qualification factors act as barriers to the inclusion of Haitian individuals in the local job market. The research revealed to us that migration and the culture of Haitians in Cuiabá - MT, especially considering access to the Portuguese language (identified here as the language of initial reception), the challenges for integration into the job market, as well as the cultural experiences and particularly the religiosity present in Haitian communities. Culture and integration into the job market act as foundations to ensure civil, political, and social rights in the migratory flow of Haitians. Participatory observation tools and semi-structured interviews wereused, which allowed for the identification of difficulties in accessing the language, especially for obtaining documents necessary for staying in Brazil and entering the world of work. These immigrants seek conditions necessary for subsistence in pastoral care and minimal training, even though they don't always contribute to the regulation as citizens. Through descriptive-analytical research with a qualitative approach to the problem, it was found that there's a lack of public policies for immigrants and little support from the State of Mato Grosso to overcome situations of labor devaluation in the world of work.